2016
DOI: 10.1063/1.4941055
|View full text |Cite
|
Sign up to set email alerts
|

CCSD(T)/CBS fragment-based calculations of lattice energy of molecular crystals

Abstract: A comparative study of the lattice energy calculations for a data set of 25 molecular crystals is performed using an additive scheme based on the individual energies of up to four-body interactions calculated using the coupled clusters with iterative treatment of single and double excitations and perturbative triples correction (CCSD(T)) with an estimated complete basis set (CBS) description. The CCSD(T)/CBS values on lattice energies are used to estimate sublimation enthalpies which are compared with critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(94 citation statements)
references
References 167 publications
0
94
0
Order By: Relevance
“…Critically assessed experimental data, used in this work as a benchmark set for validation of the computational methodology, were developed by multi-property thermodynamic correlations in our previous work 17 which provides details on this procedure and the estimation of uncertainties of reference experimental data as well as a list of primary sources of experimental 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 thermodynamic data (see Table III in ref. 17 …”
Section: Reference Experimental Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Critically assessed experimental data, used in this work as a benchmark set for validation of the computational methodology, were developed by multi-property thermodynamic correlations in our previous work 17 which provides details on this procedure and the estimation of uncertainties of reference experimental data as well as a list of primary sources of experimental 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 thermodynamic data (see Table III in ref. 17 …”
Section: Reference Experimental Datamentioning
confidence: 99%
“…Our previous study 17 and several other groups [26][27][28][29] showed that MP2 and DFT-D3 based calculations predominantly yielded overestimated cr coh E results when compared to their CCSD(T) analogues, commonly accepted as the gold standard for computational data. 30 The effect of extrapolations towards the complete basis set (CBS) 31 17,19,20,32 Using the fragment based approaches, it turns out to be important to include some of the multi-body interaction terms (typically three-body terms).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[57][58][59][60][61][62][63] The energies of monomers and spatially proximal dimers are computed via electronic structure theory, while long-range dimers and clusters consisting of larger numbers of molecules (many-body effects) are treated with a computationally inexpensive classical polarizable force field. In this work, the treatment of individual dimers (molecular pairs) was smoothly switched from quantum to classical over the intermolecular distance separation of 9 and 10 Å.…”
Section: Hmbi Calculationsmentioning
confidence: 99%